EDUKASI MANAJEMEN DAN PENCEGAHAN BULLYING DI SDN KAUM PANDAK 04 KARADENAN CIBINONG KABUPATEN BOGOR - Syaiful Anwar; Zeze Zakaria Hamzah; Muhlis Muhlis; Muchammad Hamdan; Erna Herlina; Andri Catur; Mimin Rukmini; Novita Anggraeni (LPPM Institut Pendidikan Nusantara Global, 2025)
This Community Service Program aims to strengthen the roles of teachers and parents in preventing and handling bullying among elementary school children. Using a participatory and reflective approach, the activity was carried out in the form of workshops and focus group discussions (FGDs) involving teachers and parents at SDN Kaum Pandak 04, Karadenan, Bogor Regency. The materials presented included understanding the forms and impacts of bullying, early detection techniques, intervention strategies, and empathetic communication between parents, teachers, and students. The results showed a significant improvement in participants' knowledge and skills in addressing bullying issues wisely and effectively. This activity also fostered collective awareness of the importance of school-family collaboration in creating a safe and child-friendly learning environment. The program is expected to serve as a replicable model for educational community empowerment in other schools.